Effect of oven and microwave drying on polyphenols content and antioxidant capacity of herbal tea from strobilanthes crispus leaves - Lasano, Nur Fatimah; Rahmat, Asmah; Ramli, Nurul Shazini; Abu Bakar, Mohd Fadzelly (Innovare Academic Sciences, 2018)
This study aimed to evaluate the effect of oven and microwave drying on total phenolic content (TPC), total flavonoid content (TFC), and antioxidant capacity of unfermented and fermented tea developed from Strobilanthes crispus leaves.